Migration Strategy and Diet Affect the Metabolism of Passerine Birds During Endurance Flight - Susanne Jenni‐Eiermann; Lukas Jenni (Ecology and Evolution, 2025)
ABSTRACT Bird migration varies greatly in overall distance and length of single flight bouts. Therefore, we expect that metabolic adaptations may also differ widely among migrants. Endurance flight is mainly fuelled by fat and complemented by protein. The proportions of lipids and protein accumulated before flights, and spent during flight, depend on food type. A fruit diet facilitates fattening more than a proteinous arthropod or seed diet. Adaptations to maximize lipid use during flight vary with the length of flight bouts. We expect that the type of diet and migration strategy (length of flight bouts, overall migration distance) affects flight metabolism. On a Swiss Alpine pass, we caught 30 species of nocturnal and diurnal migrant passerines out of natural migratory flight and compared them with conspecifics kept inactive. We examined the effects of migration strategy, primary diet, and body fat stores on plasma concentrations of six metabolites of the fat, protein, and carbohydrate metabolism, used as indicators of relative fuel use. During migratory flight, immediate migration strategy (short hops during day or long bouts during night), general migration strategy (long‐ and short‐distance migration) and diet affected metabolite levels, while fat stores had an additional effect. Triglyceride and free fatty acid levels were high in night‐migrants and frugivores. Uric acid and glucose levels were high in insectivores. Glucose, ß‐hydroxy‐butyrate, and glycerol were less dependent on day/night‐migration or diet. The metabolic profiles indicate that migrant passerines vary in the degree of fat use depending on migration strategy, diet, and current fat stores. Day‐migrating short‐distance migrant insectivores and granivores used protein or glycogen to a higher degree than night migrants. Frugivores maximized fat use. Long‐distance migrants favored fat use even further. Hence, long‐distance night‐migrant frugivores with high fat loads appear best adapted for fat use during migratory flight.